Heating and ventilation of school buildings - Keeler, Lot Parker (My University, 1899)
Introduction: About thirty years ago America began to realize the importance of the subjects of heating and ventilation, especially as applied to school buildings, though not until recently have these subjects received anything like the attention they deserve. A large percentage of all children under fifteen years of age spend a great part of each year inside the schoolroom, and consequently a careful study of the healthfulness of these buildings is of the utmost importance. Children during school age are in their period of most rapid bodily growth and if we would secure equally rapid mental development we must first look to their physical conditions. Both mental and spiritual growth is dependent upon the bodily conditions. The tissues of the body are being rapidly renewed and impurities are thrown off from the lungs and through the skin very rapidly. A great many children are crowded in a small space, and if the air is not frequently renewed it soon becomes extremely dangerous to health and life.
Citation: Keeler, Lot Parker. Heating and ventilation of school buildings. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Ventilation; Heating; Impure Air; Theses; Manuscripts (documents)